1971
DOI: 10.4141/cjss71-051
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Persistence of Bhc, DDT and Chlordane in a Sandy Loam Soil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…was recovered 22 weeks after its application in all the plots under different managements: STEWART and CHILSOM (1971) found that 7.5% of the technical BHC(=HCH) applied to upland fields in 1950-1953 remained in the soil even in 1968.…”
Section: Field Experimentsmentioning
confidence: 98%
See 1 more Smart Citation
“…was recovered 22 weeks after its application in all the plots under different managements: STEWART and CHILSOM (1971) found that 7.5% of the technical BHC(=HCH) applied to upland fields in 1950-1953 remained in the soil even in 1968.…”
Section: Field Experimentsmentioning
confidence: 98%
“…Consequently, many reports have been published on the persistence of this compound (YULE et aL 1967;YOSHIDA and CASTRO 1970;GUENZI et al 1971;STEWART and CHILSOM 1971;LICHTENSTEIN et aL 1971;MATHUR and SAHA 1975). It is now generally recognized that the decomposition rate of y-HCH is very slow in upland soils but relatively rapid in submerged and reduced soils.…”
mentioning
confidence: 99%
“…Published half-lives for Lindane in soil range from 4 to 6 weeks (Johri et al 1996) or 120 days (Bintein & Devillers 1996), to 260 days (Jury et al 1983) to 2 years (Johri et al 1996), depending on the method of application and application rate, as well as initial concentrations, soil differences and environmental conditions. HCH isomers, applied to field plots as a mixture of pesticide, can persist for as long as 15 years after the last application (Stewart & Chisholm 1971).…”
Section: Physical Properties and Persistence Of Hchsmentioning
confidence: 99%
“…In temperate climates, the half-life of DDT in soil has been reported to range from 2.3 to 16.7 years (Lichtenstein and Schultz 1959 ;Racke et al 1997 ;Stewart and Chisholm 1971 ).…”
Section: Levels In the Environmentmentioning
confidence: 99%
“…In general, these soils seem to exhibit a downward trend in DDT concentrations over time, which is expected given a DDT half-life of less than Sources : Unpublished technical report provided by the SARWQCB (1985); unpublished technical reports provided by The Irvine Company (1985Company ( -2006; no data were available for shaded areas and for entries noted with '--' J.L. Byard et al 55 20 years (Lichtenstein and Schultz 1959 ;Racke et al 1997 ;Stewart and Chisholm 1971 ) and the fact that DDT use was discontinued in the early 1970s. However, the data reported in Table 1 were not sampled from soils at the same locations.…”
Section: Agricultural Soilsmentioning
confidence: 99%